The Application of Advance Directives and Living Will in Persons With Dementia - Cláudia Burlá; Rui Manuel Lopes Nunes (Geriatrics, Gerontology and Aging, 2024)
The growth in world ageing is associated with an increase in life expectancy particularly in persons of more advanced ages, which expands the number of older persons with chronic-degenerative diseases, Alzheimer's disease in particular. Such individuals require specialized treatment and care. They challenge medical practice because they present multidimensional health conditions, notably cognitive impairment, which irreversibly compromises their autonomy, one of the pillars of Bioethics. In this context, this study was conducted so that, in proceeding with the search of theories, we could reflect on the loss of autonomy of the person with dementia, considering Advance Directives as an instrument provinding protection and assurance that the person's wishes will be complied with in the future. The methodology chosen was qualitative health research centered in a reflexive investigation, promoting a dialogue between biomedical facts and bioethical frameworks. For the review of literature, we examined to books and journals posted on PubMed and LILACS databases over the past 10 years. We have discussed the pertinence of Advance Directives as a successful construct of our civilization for prioritizing the autonomy of the individual and ensuring the full exercise of their rights as citizens. This instrument should be created by health older individuals prior to the development of cognitive impairment that may occur in keeping with demographic and epidemiological data. In the progressive course of dementia, even in its early stages, the recording of the person's wishes about what they want or not for themselves in terms of treatment and care is not reliable. In the conclusion of our study, we propose that Geriatrics and Bioethics be connected, so that qualified practitioners could guide older people and their family in an in-depth reflection about health and disease, autonomy and impairment, so that they can make their wishes count in an uncertain future, when they may no longer be able to make this choice themselves.